2021
DOI: 10.1002/smll.202106355
|View full text |Cite
|
Sign up to set email alerts
|

NiCo Alloy Nanoparticles on a N/C Dual‐Doped Matrix as a Cathode Catalyst for Improved Microbial Fuel Cell Performance

Abstract: The cathode material properties of the microbial fuel cell (MFC) have a quite important effect on their power generation capacity. Excellent oxygen reduction reaction (ORR) performance is the key to obtaining the remarkable capability of MFC. In this study, a series of catalysts are successfully prepared by a simple step‐by‐step hydrothermal, in situ growth, solution polymerization, and pyrolysis procedure. Here, the NiCo nanoparticles loading on nitrogen/carbon dual‐doped matrix annealing at 800 °C (NiCo@DNC‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…Meantime, the Pt 4f spectra is deconvoluted into three double peaks, indexed to Pt 0 /Pt 2+ /Pt 4+ (Figure 3b). As is shown in Table S4, it is noted that metallic state Pt presents a larger proportion compared to oxidation state, which probably can promote electrocatalytic activity improvement due to the presence of more active sites on the catalyst surface [24] . In addition, we compare the initial Pt/C with the Pt 4f peak of the PtCo@NC‐X sample.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Meantime, the Pt 4f spectra is deconvoluted into three double peaks, indexed to Pt 0 /Pt 2+ /Pt 4+ (Figure 3b). As is shown in Table S4, it is noted that metallic state Pt presents a larger proportion compared to oxidation state, which probably can promote electrocatalytic activity improvement due to the presence of more active sites on the catalyst surface [24] . In addition, we compare the initial Pt/C with the Pt 4f peak of the PtCo@NC‐X sample.…”
Section: Resultsmentioning
confidence: 98%
“…As is shown in Table S4, it is noted that metallic state Pt presents a larger proportion compared to oxidation state, which probably can promote electrocatalytic activity improvement due to the presence of more active sites on the catalyst surface. [24] In addition, we compare the initial Pt/ C with the Pt 4f peak of the PtCo@NC-X sample. The Pt 4f7/2 peaks of the as-synthesized PtCo@NC-X samples display different positive shift degrees relative to Pt/C catalyst, which is evaluated as ~0.194 eV for PtCo@NC-40, ~0.462 eV for PtCo@60 and ~0.241 eV for PtCo@80 catalyst (Figure 4a).…”
Section: Resultsmentioning
confidence: 99%
“…The higher activity resulted from the double Co site of 001 face present in the catalyst (Lin et al, 2021). The NiCo alloy on N-doped carbon showed excellent ORR activity and showed a 2.16 times higher maximum power density of 2,325.60 mW m -2 than that of the Pt/C catalyst which was due to the synergistic effect of NiCo active sites, and graphitic and pyridinic N (Huang et al, 2022).…”
Section: Figurementioning
confidence: 98%
“…[13][14][15] We have modified semiconductor metal oxide materials with different noble metals, but the experimental results showed that it cannot meet our needs for efficient and specific detection of F-type greenhouse gases. Non-metal element-doped semiconductor metal oxides have been widely used in catalysis, [16][17][18][19][20] and have also been tentatively utilized in gas detection as gas sensing materials. For example, the surface of TiO 2 was modified by codoping with N and F, and three kinds of SF 6 decomposition components (SO 2 , SOF 2 and SO 2 F 2 ) were detected.…”
Section: Introductionmentioning
confidence: 99%